Football and Dementia: Understanding the Link - Neal, James; Hutchings, Paul B.; Phelps, Ceri; Williams, Donald (Frontiers in Psychiatry, 2022)
Football, also known as soccer or association football, is popular but has a potential link with dementia developing in retired players. The FA and soccer regulators in the USA have imposed guidelines limiting players exposure to heading, despite controversy whether this dementia is caused by heading the ball, a form of mild repetitive head injury (RHI), over many years. Substantial data exist showing that many ex-North American Football players develop a specific neurodegenerative disease: chronic traumatic encephalopathy (CTE), the neuropathological disorder of boxers. In the United Kingdom evidence for the neuropathological basis of footballers' dementia has been slow to emerge. A 2017 study revealed that in six ex-soccer players four had CTE with Alzheimer's disease (AD) and two had AD. A 2019 study showed that ex-footballers were 3.5 times more likely to die from dementia or other neuro-degenerative diseases than matched controls. We argue that in childhood and adolescence the brain is vulnerable to heading, predicated on its disproportionate size and developmental immaturity. RHI in young individuals is associated with early neuroinflammation, a potential trigger for promoting neurodegeneration in later life. Evidence is available to support the guidelines limiting heading for players of all ages, while professional and non-players should be included in prospective studies to investigate the link between soccer and dementia.